Use of acellular dermal matrices in laryngotracheal and pharyngeal reconstruction: systematic review. Issue 7 (15th May 2017) - Hui, A; Hong, P; Bezuhly, M
Abstract: Background: Acellular dermal matrices are increasingly used in laryngotracheal and pharyngeal reconstruction, but specific indications and the type of acellular dermal matrix used vary. The authors systematically reviewed outcomes relating to acellular dermal matrix use in head and neck reconstruction. Methods: Electronic databases were searched through 1 May 2016 for literature on acellular dermal matrix use in laryngotracheal and pharyngeal reconstruction. Studies were appraised for surgical indications, outcomes and study design. Results: Eleven publications with 170 cases were included. Eight articles reported on acellular dermal matrix use in oncological reconstruction. Most studies were case series; no high-level evidence studies were identified. Graft extrusion was more common in non-oncological applications. In general, post-oncological reconstruction with an acellular dermal matrix demonstrated complication rates similar to those reported without an acellular dermal matrix. Conclusion: Evidence in support of acellular dermal matrix use in head and neck reconstruction is generally poor. Prospective comparative studies are required to define the indications, safety and effectiveness of acellular dermal matrices in laryngotracheal and pharyngeal reconstruction.